2019
DOI: 10.1016/j.nicl.2018.11.006
|View full text |Cite
|
Sign up to set email alerts
|

White matter injury predicts disrupted functional connectivity and microstructure in very preterm born neonates

Abstract: ObjectiveTo determine whether the spatial extent and location of early-identified punctate white matter injury (WMI) is associated with regionally-specific disruptions in thalamocortical-connectivity in very-preterm born neonates.Methods37 very-preterm born neonates (median gestational age: 28.1 weeks; interquartile range [IQR]: 27–30) underwent early MRI (median age 32.9 weeks; IQR: 32–35), and WMI was identified in 13 (35%) neonates. Structural T1-weighted, resting-state functional Magnetic Resonance Imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…Given its pivotal role in facilitating cross-talk between cerebral hemispheres, aberrant CC development or injury may translate to altered motor and cognitive functional circuitry later in life [57][58][59][60] . Notably, former very premature neonates with white matter injury in the CC were shown to exhibit altered intrinsic functional connectivity between thalamic and sensorimotor networks 61 . Future studies of the CC should include complementary diffusion tensor imaging (DTI) analyses such as regional white matter measurements of fractional anisotropy and mean diffusivity as indicators of white matter microstructural integrity in the setting of perioperative critical care in infancy.…”
Section: Discussionmentioning
confidence: 99%
“…Given its pivotal role in facilitating cross-talk between cerebral hemispheres, aberrant CC development or injury may translate to altered motor and cognitive functional circuitry later in life [57][58][59][60] . Notably, former very premature neonates with white matter injury in the CC were shown to exhibit altered intrinsic functional connectivity between thalamic and sensorimotor networks 61 . Future studies of the CC should include complementary diffusion tensor imaging (DTI) analyses such as regional white matter measurements of fractional anisotropy and mean diffusivity as indicators of white matter microstructural integrity in the setting of perioperative critical care in infancy.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in the Introduction, EoP that covers the different injury patterns related to premature birth can affect either the WM or GM but, depending on the nature and the severity of the lesion, the extent of brain lesions could vary strongly between the individuals. With new emerging MRI techniques, better characterization of EoP now became possible and opens new understanding, such as functional connectivity, diffusion tensor imaging, fractional anisotropy measures and fiber tractography, and automated segmentation techniques for volume determination and growth (Ball et al, 2013;Gozdas et al, 2018;Schneider et al, 2018;Duerden et al, 2019;Jakab et al, 2019). The most prominent findings of EoP in VPT are (1) decreased global brain volume due to white (WM) and gray matter reduction [(GM); cortical GM as well as deep nuclear GM], (2) hydrocephalus ex vacuo (CSF), and (3) connectivity impairment (Dubois et al, 2008;Ball et al, 2013;Chau et al, 2013;Kidokoro et al, 2013;Friedrichs-Maeder et al, 2017;Gozdas et al, 2018;Duerden et al, 2019;Jakab et al, 2019).…”
Section: Encephalopathy Of the Prematurity In Humans And Evidence Of mentioning
confidence: 99%
“…Despite the increasing evidence that repeated painful experiences during the first days of life in the neonatal intensive care environment may contribute to structural alterations of the preterm neonatal brain, little research has focused on the relationship between painful stressors and functional activity of the preterm brain at term corrected age (Smith et al, 2011). Recent studies demonstrated weaker functional connectivity in preterm neonates evaluated at term corrected age, with more severe alterations of network complexity in neonates with white matter injuries (Ball et al, 2016; Scheinost et al, 2016; Duerden et al, 2019). Nevertheless, little is known on the extent to which painful stressors may affect brain connectivity in these early phases, with potential consequences on future brain development, and plasticity.…”
Section: Introductionmentioning
confidence: 99%